Haptic Surface Display based on Miniature Dielectric Fluid Transducers - Han, Amy Kyungwon; Ji, Sheng; Wang, Dangxiao; Cutkosky, Mark R (IEEE robotics and automation letters, 2020)
We present a lightweight, low power, and compliant miniature dielectric fluid transducer intended for haptic surface display. The actuator has a large strain and fast response without an external compressor. It consists of a thin oil-filled pouch with a 1.5 mm diameter opening covered with a silicone membrane. The application of voltage causes the pouch to squeeze the oil and form a bump by stretching the silicone membrane. The actuator produces 1.45 mm bump height at 3 kV and 13 mN at 3.5 kV using ≈ \text{10}\,μ l of oil. The power consumption is < 3 mW. Though the largest bump height has a bandwidth near 5 Hz, the device achieves perceivable vibration at 200 Hz with a bump height of 200 μ m. The actuators can be packed closely and controlled individually to create dynamic texture displays, suitable for active surface exploration with the fingertips. The simulation results show the width of the actuator can be reduced without affecting the performance. Tests with human subjects show that users differentiated simple bump patterns with a 98.8% success rate.